Young children's video/computer game use: relations with school performance and behavior. - Hastings EC; Karas TL; Winsler A; Way E; Madigan A; Tyler S (Issues in Mental Health Nursing, 2009)
This study examined the amount and content of children's video game playing in relation with behavioral and academic outcomes. Relationships among playing context, child gender, and parental monitoring were explored. Data were obtained through parent report of child's game play, behavior, and school performance. Results revealed that time spent playing games was related positively to aggression and negatively to school competence. Violent content was correlated positively and educational content negatively with attention problems. Educational games were related to good academic achievement. Results suggest violent games, and a large amount of game play, are related to troublesome behavioral and academic outcomes, but educational games may be related to positive outcomes. Neither gender nor parental monitoring emerged as significant moderators of these effects.